Arabic Christianity between the Ottoman Levant and Eastern Europe - Feodorov, Ioana; Heyberger, Bernard; Noble, Samuel (Arabic Christianity, 2021)
This volume sheds light on the historical background and political circumstances that encouraged the dialogue between Eastern-European Christians and Arabic-speaking Christians of the Middle East in Ottoman times, as well as the means employed in pursuing this dialogue for several centuries. The ties that connected Eastern European Christianity with Arabic-speaking Christians in the 16th-19th centuries are the focus of this book. Contributors address the Arabic-speaking hierarchs' and scholars' connections with patriarchs and rulers of Constantinople, the Romanian Principalities, Kyiv, and the Tsardom of Moscow, the circulation of literature, models, iconography, and knowhow between the Middle East and Eastern Europe, and research dedicated to them by Eastern European scholars. Contributors are Stefano Di Pietrantonio, Ioana Feodorov, Serge Frantsouzoff, Bernard Heyberger, Elena Korovtchenko, Sofia Melikyan, Charbel Nassif, Constantin A. Panchenko, Yulia Petrova, Vera Tchentsova, Mihai Ţipău and Carsten Walbiner.